MANFAAT DIGITAL MARKETING PADA PEMILIK USAHA DI KOTA BENGKULU - Afriani, Sulisti; Yanti, Rina Trisna; Revolina, Ellya (JURNAL ILMIAH EDUNOMIKA, 2024)
This research was conducted on 27 business owners, data collection was carried out by distributing questionnaires using Google Form. From the results of research that has been carried out, it can be concluded that 66.7% think digital marketing has an important role, one of which is helping to expand marketing reach. The benefits of digital marketing for business owners have the same two values, namely 37%, namely each of them thinks that digital marketing provides benefits for their business in terms of building interactions with customers and increasing marketing distribution channels for the products/services they sell and business owners get digital benefits marketing especially they feel comfortable and can be done 24 hours any time anywhere with a value of 77.8%. Keywords : digital marketing